An ethnographic investigation of maternity healthcare experience of immigrants in rural and urban Alberta, Canada - Higginbottom, Gina M.A.; Safipour, Jalal; Yohani, Sophie; O'Brien, Beverley; Mumtaz, Zubia; Paton, Patricia; Chiu, Yvonne; Barolia, Rubina (BioMed Central, 2016)
Background: Canada is among the top immigrant-receiving nations in the world. Immigrant populations may face structural and individual barriers in the access to and navigation of healthcare services in a new country. The aims of the study were to (1) generate new understanding of the processes that perpetuate immigrant disadvantages in maternity healthcare, and (2) devise potential interventions that might improve maternity experiences and outcomes for immigrant women in Canada.